2010
DOI: 10.1007/s10071-010-0365-2
|View full text |Cite
|
Sign up to set email alerts
|

Sequential planning in rhesus monkeys (Macaca mulatta)

Abstract: In the current study, we examined the planning abilities of rhesus monkeys (Macaca mulatta) by training them on a five-item list composed of coloured photographs and then testing them on switch and mask trials. In contrast to previous studies where monkeys made responses using a joystick, in the current study, monkeys made responses directly to a touch screen. On switch trials, after a response to the first list item, the on-screen positions of two list items were exchanged. Performance on trials in which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 33 publications
6
24
0
Order By: Relevance
“…Other evidence collected using the SimChain paradigm suggests that macaques rarely plan their response more than one response in advance (Scarf et al 2011), consistent with an earlier finding suggesting limited planning in both macaques and chimpanzees (Beran et al 2004). These results support the view that non-human primates engage in cognitive tasks with a minimal reliance on queuing processes.…”
Section: Discussionsupporting
confidence: 81%
“…Other evidence collected using the SimChain paradigm suggests that macaques rarely plan their response more than one response in advance (Scarf et al 2011), consistent with an earlier finding suggesting limited planning in both macaques and chimpanzees (Beran et al 2004). These results support the view that non-human primates engage in cognitive tasks with a minimal reliance on queuing processes.…”
Section: Discussionsupporting
confidence: 81%
“…SimChain completion utilizes a series of planned responses (Scarf, Danly, Morgan, Colombo, & Terrace, 2011), but apart from the pause before the initial response, wherein the chain planning pauses occur depends on the individual animal. We analyzed the first response RT for only correct responses, as well as the RT for all first responses, to search for speed-accuracy trade-offs (Prinzmetal, McCool, & Park, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…To determine this, mask trials were needed so that it would be clear how far into a planned sequence the monkeys would go at the outset of trials. Again, previous research has been unclear on this issue, with some studies showing performance that would seem to indicate that the entire sequence was planned (e.g., Kawai and Matsuzawa 2000), whereas other studies show much more limited planning, and mainly just for one selection beyond the current one (e.g., Beran et al 2004; Scarf et al 2011). Experiment 2 tested this in the capuchin monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…As with the primates tested by Beran et al (2004), planning was limited among the pigeons, but still evident, as only one masked item was selected at above chance levels, and the shift trials also had the same detrimental effects seen in primates (e.g., Beran et al 2004; Biro and Matsuzawa 1999). In addition, Scarf, Danly, Morgan, Colombo, and Terrace (2011) reported that shifts of the stimuli in positions three and four in the sequence after choice of the first stimulus had little or no effect on performance of monkeys, further indicating that they were not planning the entire sequence of responses at the outset of trials. Thus, one might assume that these results suggest similarities across a broad range of species for this type of planning behavior, with evidence of only limited planning in a sequence task.…”
Section: Introductionmentioning
confidence: 99%